2021
DOI: 10.18632/aging.202811
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic analysis of tumor mutation burden and immune infiltration in hepatocellular carcinoma based on TCGA data

Abstract: In order to explore the prognosis of tumor mutation burden (TMB) and the relationship with tumor infiltrating immune cells in hepatocellular carcinoma (HCC), we downloaded somatic mutation data and transcriptome profiles of 376 HCC patients from The Cancer Genome Atlas (TCGA) cohort. We divided the samples into high-TMB and low-TMB groups. A higher TMB level indicated improved overall survival (OS) and was associated with early pathological stages. One hundred and nine differentially expressed genes (DEGs) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…Unfortunately, however, few clinical studies have revealed the role of TMB in HCC. We and others found a significant correlation between TMB and immune infiltration in HCC ( 5 ā€“ 7 ). Most importantly, the PS model was significantly associated with TMB and immune infiltration.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Unfortunately, however, few clinical studies have revealed the role of TMB in HCC. We and others found a significant correlation between TMB and immune infiltration in HCC ( 5 ā€“ 7 ). Most importantly, the PS model was significantly associated with TMB and immune infiltration.…”
Section: Discussionsupporting
confidence: 64%
“…A detailed understanding of the mechanism underlying immune infiltration may favor precision immunotherapy in HCC. Tumor mutation burden (TMB) refers to the total number of mutations in the coding region of the evaluated gene in the tumor cell (TC) genome, which is calculated by the total number of mutations per megabase in the genome (5)(6)(7). Previous reports suggested the close association of TMB with immune infiltration, while the molecular mechanism remains inconclusive (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Then, we calculated the panel-TMB for each sample as the total amount of coding variants/exons length (38 million) based on the number of non-synonymous somatic mutations, including frameshift deletion mutation, in-frame deletion mutation, frameshift insertion mutation, in-frame insertion mutation, missense mutation, nonsense mutation, nonstop mutation, and silent mutation. Using median as the threshold, patients were divided into high TMB group and low TMB group (27).…”
Section: Correlation Analysis Between Tmb and Overall Survival (Os)mentioning
confidence: 99%
“…We determined the median value as the threshold for panel- KMT2C [38] FCGR2A [37] MYC [35] NCOR1 [33] CHD4 [32] HLA-B [32] KMT2D [32] SPEN [32] NOTCH2 [27] BCR [26] KMT2B [26] MAP3K1 [25] HLA-A [23] LRP1B [23] NOTCH1 [23] TP53 [23] FAT1 [22] KAT6A [21] PED4DIP [21] PRSS1 [21] ARID1A [20] ARID1B [20] CIC [20] HLA-DRB51 [20] FAT3 [ A-DRB5 [20] ClC [20] ARID1B [20] ARID1A [20] PRSS1 [21] PED4DIP [21] KAT6A [21] FAT1 [22] TP53 [23] NOTCH1 [23] LRP1B [23] HLA-A [23] MAP3K1 [25] KMT2B [26] BCR [26] NOTCH2 [27] SPEN [32] KMT2D [32] HLA-B [32] CHD4 [32] NCOR1 [33] MYC [35] FCGR2A [37] KMT2C [38]<...>…”
Section: Higher Tmb Estimated By the Panel-tmb Is Associated With Improved Osmentioning
confidence: 99%
“…Tumor microenvironment has been brought into focus in the progression of cancer for a long time, especially immune in ltrates [52]. Tumor-in ltrating immune cells (TIICs) have close connection with prognosis in various cancers [53,54]. In our study, we detected that ARMC10 expression was positively relevant to the in ltration of Th2 cells, T helper cells and negatively relevant to pDC cells in ltration.…”
Section: Discussionmentioning
confidence: 59%